Infrared emission towards SN 1987A 11 years after outburst: measurements with ISOCAM - Fischera, Jörg; Tuffs, Richard J.; Völk, Heinrich J. (Astronomy and astrophysics, 2002)
We present measurements of the mid-infrared (MIR) emission from SN 1987A, made using the Infrared Space Observatory (ISO) 11 years after outburst. They are the only late epoch detections of this source in the thermal IR regime. The position of the source, determined from an offset to an IR-emitting star, suggests that the emission is associated with SN 1987A or its extended supernova remnant (SNR). A predominantly circumstellar origin is however suggested by the size and orientation of the IR-emitting region, which is comparable with the extension of the inner ring seen with the Hubble Space Telescope (HST). The emission is most probably from collisionally-heated circumstellar grains embedded in shocked gas downstream of the blast wave. The MIR extent is consistent with the hypothesis that the blast wave was propagating into material of moderate density interior to the thick inner ring at the epoch of the ISOCAM observations.
Gesehen am 01.12.2020